BCL11B Regulates Arterial Stiffness and Related Target Organ Damage. Issue 6 (3rd February 2021) - Valisno, Jeff Arni C.; May, Joel; Singh, Kuldeep; Helm, Eric Y.; Venegas, Lisia; Budbazar, Enkhjargal; Goodman, Jena B.; Nicholson, Christopher J.; Avram, Dorina; Cohen, Richard A.; Mitchell, Gary F.; Morgan, Kathleen G.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: BCL11B (B-cell leukemia 11b) is a transcription factor known as an essential regulator of T lymphocytes and neuronal development during embryogenesis. A genome-wide association study showed that a gene desert region downstream of BCL11B, known to function as a BCL11B enhancer, harbors single nucleotide polymorphisms associated with increased arterial stiffness. However, a role for BCL11B in the adult cardiovascular system is unknown. Objective: Based on these human findings, we sought to examine the relation between BCL11B and arterial function. Methods and Results: Here we report that BCL11B is expressed in the vascular smooth muscle where it regulates vascular stiffness. RNA sequencing of aortas from wild-type and Bcl11b null mice (BSMKO) identified the cGMP (cyclic guanosine monophosphate)-cGMP-dependent protein kinase G (PKG) as the most significant differentially regulated signaling pathway in BSMKO compared with wild-type mice. BSMKO aortas showed decreased levels of PKG1, increased levels of Ca ++ -calmodulin-dependent serine/threonine phosphatase calcineurin (PP2B) and decreased levels of their common phosphorylation target, phosphorylated vasodilator-stimulated phosphoprotein (pVASP S239 ), a regulator of cytoskelatal actin rearrangements. Decreased pVASP S239 in BSMKO aortas was associated with increased actin polymerization (filamentous/globular actin ratio). Functionally, aortic force, stress, wall tension, and stiffness, measured ex vivo in organ baths, were increased in BSMKO aortas, and BSMKO mice had increased pulse wave velocity, the in vivo index of arterial stiffness. Despite having no effect on blood pressure or microalbuminuria, increased arterial stiffness in BSMKO mice was associated with increased incidence of cerebral microbleeds compared with age-matched wild-type littermates. Conclusions: We have identified vascular smooth muscle BCL11B as a crucial regulator of aortic smooth muscle function and a potential therapeutic target for vascular stiffness.